2022
DOI: 10.1139/as-2020-0057
|View full text |Cite
|
Sign up to set email alerts
|

Can bryophyte groups increase functional resolution in tundra ecosystems?

Abstract: The relative contribution of bryophytes to plant diversity, primary productivity, and ecosystem functioning increases towards colder climates. Bryophytes respond to environmental changes at the species level, but because bryophyte species are relatively difficult to identify, they are often lumped into one functional group. Consequently, bryophyte function remains poorly resolved. Here, we explore how higher resolution of bryophyte functional diversity can be encouraged and implemented in tundra ecological stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 99 publications
1
21
0
Order By: Relevance
“…Within Russia, there is a great expertise in taxonomy and systematics. While many researchers are developing methods to classify bryophytes into functional groups for studying ecosystem-level processes because of difficulty of identification in the field (Lett et al 2021, Siberian researchers focus on detailed species-level identifications (e.g. Volkova et al 2021) which adds to the understanding of baseline biodiversity and current dynamics.…”
Section: Biodiversitymentioning
confidence: 99%
“…Within Russia, there is a great expertise in taxonomy and systematics. While many researchers are developing methods to classify bryophytes into functional groups for studying ecosystem-level processes because of difficulty of identification in the field (Lett et al 2021, Siberian researchers focus on detailed species-level identifications (e.g. Volkova et al 2021) which adds to the understanding of baseline biodiversity and current dynamics.…”
Section: Biodiversitymentioning
confidence: 99%
“…Bryophyte sods have been used with considerable success in assisted revegetation of tundra wetlands affected by vehicle tracks in the Canadian High Arctic (Forbes 1993). This shows that we need a better understanding of the highly significant bryophyte component when conducting future studies on regeneration of High Arctic disturbances (Lett et al 2021;Mörsdorf and Cooper 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous studies in mountain regions of Siberia [44], our study has revealed that the plant communities of bryophytes could be better indicators of environmental conditions than that of the vascular plants. The relative contribution of bryophytes to plant diversity, net primary production of mires, and ecosystem functions increases towards colder climates, and local permafrost of the mountain palsa mire accelerate this effect [75].…”
Section: Current State Of Permafrost and Adjacent Vegetationmentioning
confidence: 99%